Evaluation of operating performance and level of service of urban public transport in Kerman, Iran - Najafabadipour, Tooraj (2011)
Everywhere in the world public transport faces serious competition from private vehicles, especially in Iran where fuel price is extremely low. To sustain, it should offer high quality service with good operating performance and keep the fares low. This study attempts to evaluate the operating performance and level of service of the urban bus in Kerman, to identify suitable remedial measures. Data for analysis was collected through interview with Kerman Bus Organization staff, previous reports on various urban transportation studies in Iran, observation of the bus operation, and survey of bus patronage and passenger satisfaction using questionnaires. Results of the study in bus performance and level of service are classified into 3 categories: (1) out of standard and therefore not acceptable: average number of passengers per bus per day (736, standard 1000-1200), fleet utilization (74% , standard 80-90%), average distance travelled per bus per day (88 km, standard 210- 260 km), breakdown in service (19.6%, standard 8-10%), staff ratio (2.09, standard 3-8), dead mileage (20.85 %, standard 0.6-1.00%), operating ratio (0.92, standard 1.05-1.08), interchange between routes and services more than once (51%, standard < 10%), load factor (over-loading in Line 101, under-capacity in other lines; (2)within standard: administrative staff ratio (0.3-0.4), fuel sumption (25-50 litres per 100km), walking distance to bus stop, journey time, load factor in Line 139; and (3) out of standard but still acceptable: average number of passengers per bus per day in Lines 101, 102 and 103 (1870, 1203 and 1377 respectively, standard 1000-1200). Data analyses using Rasch method on passenger satisfaction reveals that, on average, passengers are unhappy with the bus services provided (N = 400, logit = -0.65) and can be classified into 5 groups: very happy (n = 5, logit > 0.45), happy (n = 24, 0 < logit < 0.45), unhappy (n = 169, -0.65 < logit <0), very unhappy (n = 161, -1.19 < logit < -0.65) and finally, totally unhappy (n = 41, logit < -1.19). Further, based on the Rasch analysis, this study shows that, among the bus service attributes, the followings need immediate improvement: bus timeliness, security in the bus and adequacy of information at the bus stops. Consequently, by evaluating the bus services in Kerman using most indicators as recommended by the World Bank, this research has important implication for future practices by decision makers and bus operators to improve quality of the services for greater passengers’ satisfaction not only in Iran but also in other parts of the world.